Islam and Evolution Al-Ghazālī and the Modern Evolutionary Paradigm - Malik, Shoaib Ahmad (Routledge Science and Religion Series, 2021)
"This book attempts to equip the reader with a holistic and accessible account of Islam and evolution. It guides the reader through the different variables that have played a part in the ongoing dialogue between Muslim creationists and evolutionists. This work views the discussion through the lens of al-Ghazālī (1058-1111), a widely-known and well-respected Islamic intellectual from the medieval period. By understanding al-Ghazālī as an Ash'arite theologian, a particular strand of Sunni theology, his metaphysical and hermeneutic ideas are taken to explore if and how much Neo-Darwinian evolution can be accepted. It is shown that his ideas can be used to reach an alignment between Islam and Neo-Darwinian evolution. This book offers a detailed examination that seeks to offer clarity if not agreement in the midst of an intense intellectual conflict and polarity amongst Muslims. As such, it will be of great interest to scholars of Science and Religion, Theology, Philosophy of Religion, Islamic Studies, and Religious Studies more generally. "